TRAUMATIC ABDOMINAL WALL HERNIA ; A CASE REPORT - Mihajlova, Nikolina; Janik, Violeta; Dukovska, Vesna; Cvetanovski, Vlatko; Mitevski, Aleksandar (Journal of Morphological Sciences; Vol 8 No 1 (2025): JMS, 2025)
Traumatic abdominal wall hernia remains a rarely reported event, despite the high prevalence of blunt abdominal trauma. The traumatic abdominal wall hernia  was successfully managed by Intra peritoneal On lay Mesh technique, a repair procedure where a mesh is introduced into the abdominal cavity and placed from the inside over the hernia opening. Case report :  We report a rare case of traumatic abdominal wall hernia caused by a traffic accident. A 33-year-old male was hospitalized after road traffic accident. He sustained facial and rib fractures and received emergency treatment and was presumably discharged after reasonable recovery. He attended our clinic two years later with complaints of pain and swelling in the left subcostal area. Computed tomography  showed an abdominal wall defect. Type of abdominal wall, the size of the hernia defect and the presence of associated intra-abdominal injuries are main factors to decide how the hernia will be repaired, immediate versus delayed. IPOM plus technique is used in an elective treatment of traumatic abdominal wall hernias. Studies show that seroma formation was less often found   in patients undergoing laparoscopic intra peritoneal on lay mesh treatment with fascial defect closure as compared to laparoscopic intra peritoneal on lay mesh placement  without defect closure. Traumatic abdominal wall hernia presents a diagnostic as well as a therapeutic challenge. The therapeutic approach is governed by a multitude of factors emphasizing the need of a patient-tailored, case by case management plan.   Keywords: trauma, hernia, IPOM, hernioplasty, mesh